Assessment of the urban center condition a proposed physical regeneration in Davao City old street applying the new urbanism principles - Ching, Neice Joy D.; Sebastian, Myrafe L. (2015)
The research entitled Assessment of the Urban Center Condition: A Proposed Physical Regeneration in Davao City Old Street Applying the New Urbanism Principles is a study conducted to primarily assess the existing condition of the physical stocks of the six old streets in the urban center of Davao City in which the results of the assessment are essential to the physical regeneration of the old street. The physical regeneration took place in the least adaptive old street based on the result which was incorporated with valuable architectural concepts and new urbanism principles to address the existing problems and to uplift is urban image as well. The researcher utilized a descriptive qualitative approach in the study which included a content analysis on the existing condition of the physical stocks in the six old streets as represented by the quality of the profiles of the buildings and its site. The researcher also conducted an interview to determine the existing problems in the site. With the support of the architectural concepts and new urbanism principles, the researcher formulated the design solutions and design guidelines to address the identified problems in the study. As the data were analyzed, it have led to the result that the Ramon Magsaysay Avenue has the least adaptability. Considering the gathered data in the study, maintenance and quality architecture of the physical stocks with an incorporated theme are essential in the regeneration process of its area. In conclusion, an urban image along with the vital architectural concepts and new urbanism principles are the desirable considerations for the practice of physical regeneration.
Thesis (BS Architecture) -- University of the Philippines Mindanao, 2015